1969
DOI: 10.1677/joe.0.0450083
|View full text |Cite
|
Sign up to set email alerts
|

The Release of Antidiuretic Hormone From the Pituitary Stalk After Intravenous Calcium Chloride or Magnesium Chloride Infusion in Rats

Abstract: Experiments were performed on male albino rats in urethane anaesthesia. The pituitary gland was exposed, the pituitary stalk was cut and the whole gland was removed. Isotonic sodium chloride solution used for washing the cut pituitary stalk was collected and its antidiuretic activity assayed. Antidiuretic substance was liberated from the infundibular axons into the washing fluid during continuous intravenous infusion of a hypotonic saline. The antidiuretic activity of the washing fluid was assayed in ethanol-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

1971
1971
1985
1985

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…The outflow of VP from cut axons of the SOHT has been estimated to be 80 pg/h (Lesnik et al 1969) and this is clearly not sufficient to account for the present values of approximately 1 -25 ng VP/h in hypo¬ physial portal plasma. Thus, the high concentrations of VP and OT in hypophysial portal blood are due to the direct release of these nonapeptides into the hypo¬ physial portal vessels.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…The outflow of VP from cut axons of the SOHT has been estimated to be 80 pg/h (Lesnik et al 1969) and this is clearly not sufficient to account for the present values of approximately 1 -25 ng VP/h in hypo¬ physial portal plasma. Thus, the high concentrations of VP and OT in hypophysial portal blood are due to the direct release of these nonapeptides into the hypo¬ physial portal vessels.…”
Section: Resultscontrasting
confidence: 62%
“…The plasma concentrations of OT were similar to those reported recently by Gibbs (1984) who collected portal blood by the method of Porter & Smith (1967). The high concentrations of VP in hypophysial portal plasma could be due to the direct release of VP into hypophysial portal blood, the presence of VP in blood arising from backflow from the posterior pituitary gland (Oliver et al 1977;Bergland & Page, 1978), the presence of VP in cerebrospinal fluid (CSF) (Dogterom, van Wimersma Greidanus & De Wied, 1978) or the leakage of VP from cut axons of the SOHT (Lesnik et al 1969). It is unlikely that a significant amount of either VP or OT in hypophysial portal plasma is due to backflow of blood from the posterior pituitary gland, since the present studies showed that there was no significant change in the concentration of either peptide in hypophysial portal plasma from animals in which the pituitary gland had been removed at the time of pituitary stalk section compared with concentrations in hypophysial portal plasma from animals in which the pituitary gland had been left in situ (Text- fig.…”
Section: Resultsmentioning
confidence: 84%
“…injection of 1 ml Locke solution containing additionally 60 /iM-CaCl2, induces an enhanced release of antidiuretic activity from the hypothalamic end of the cut rat pituitary stalk (Lesnik, Guzek & Traczyk, 1969). The same amount of CaCl2 was injected i.v.…”
Section: Discussionmentioning
confidence: 99%
“…T OM as/T raczyk/G uzek in a variety of situations [LeSnik et al, 1969]. The present study deals with the influence of hippocampal stimulation on the release of ADS from the cut pituitary stalk and on the rate of urine flow.…”
mentioning
confidence: 98%